2018
DOI: 10.1177/0030222818782344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Contents in Advance Directives on Individuals’ Decision-Making

Abstract: Completing an advance directive offers individuals the opportunity to make informed choices about end-of-life care. However, these decisions could be influenced in different ways depending on how the information is presented. We randomly presented 185 participants with four distinct types of advance directive: neutrally framed (as reference), negatively framed, religiously framed, and a combination. Participants were asked which interventions they would like to receive at the end of life. Between 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…By contrast, men tend to follow professionals' opinions and accept aggressive treatments than women 26 . This phenomenon may be related to traditional gender roles and social expectations 24 …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…By contrast, men tend to follow professionals' opinions and accept aggressive treatments than women 26 . This phenomenon may be related to traditional gender roles and social expectations 24 …”
Section: Discussionmentioning
confidence: 97%
“…Previous studies on older adults have shown that sex affects their perceptions of EOL care. 3,[21][22][23][24][25] One study indicated that women were more likely to refuse special life-sustaining treatment, such as CPR and ventilator, than men. 24 Another study in Switzerland showed that women had higher AD awareness and completion levels than men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En concordancia con lo dicho, Toro et al recomiendan que los profesionales sanitarios "mejoren su conocimiento sobre este tema para poder ayudar a sus pacientes a hacer realidad sus instrucciones previas" (13, p. 406), puesto que el contenido del dva puede tener repercusiones en la toma de decisiones frente a esta práctica. Así lo demostraron Park et al (46) en su estudio acerca del efecto del contenido del dva en la toma de decisiones individuales frente al mismo; un alto porcentaje de participantes rechazaron las opciones de va expresadas en el documento cuando estas fueron expresadas en términos negativos. Mientras que otro porcentaje de participantes presentó un alto grado de indecisión a causa de los términos religiosos incluidos en el dva.…”
Section: Discussionunclassified